Studies on Phytochemicals and Antimicrobial Evaluation of Flower Extract of Spathodea Campanulata - J, Gani; I, Nkafamiya I.; A, Akinterinwa (Darul Yasin Al Sys, 2024)
Spathodea campanulata is a medicinal plant useful in traditional medicine for the treatment and prevention of some diseases of bacterial and none microbial origins. As a result of this, it becomes very important to investigate the phytochemical and antimicrobial activities of the flower extract. 200 g of S. campanulata air dried flower ground to powder was extracted with methanol. The flower extracts showed qualitatively the presence of saponin, steroid, flavonoids, alkaloids, phenol, tannin, and terpenoids while glycosides were absent. S. camapanulata exhibits selective antimicrobial properties, being particularly effective against Staphylococcus and somewhat against Pseudomonas, but showing no significant activity against Candida or Aspergillus.